A one‐step assay for sorted CD3+ cell purity and chimerism after hematopoietic stem cell transplantation. (29th December 2020) - Desoutter, Judith; Usureau, Cédric; Jacob, Valentine; Lebon, Delphine; Caulier, Alexis; Da Costa, Cécilia; Charbonnier, Amandine; Joris, Magalie; Marolleau, Jean‐Pierre; Guillaume, Nicolas
Abstract : A hematopoietic chimerism assay is the laboratory test for monitoring engraftment and quantifying the proportions of donor and recipient cells after hematopoietic stem cell transplantation recipients. Flow cytometry is the reference method for determining the purity of CD3 + cells on the chimerism of selected CD3 + cells. In the present study, we developed a single‐step procedure that combines the CD3 + purity assay (using the PCR‐based Non‐T Genomic Detection Kit from Accumol, Calgary, Canada) and the qPCR chimerism monitoring assay (the QTRACE qPCR assay from Jeta Molecular, Utrecht, the Netherlands). First, for the CD3 + purity assay, we used a PCR‐friendly protocol by changing the composition of the ready‐to‐use reaction tubes (buffer and taq polymerase) and obtained a satisfactory calibration plot ( R 2 = 0.8924) with a DNA reference scale of 2 ng/μl. Next, 29 samples (before and after CD3 positive selection) were analyzed, the mean cell purity was, respectively, 19.6% ± 6.45 and 98.9% ± 1.07 in the flow cytometry assay; 26.8% ± 7.63 and 98.5% ± 1.79 in the PCR‐based non‐T genomic detection assay. Our results showed that the CD3 + purity assay using a qPCR kit is a robust alternative to the flow cytometry assay and is associated with time savings when combined with a qPCR chimerism assay.